Evaluation of Writing Skills (Imla) of Grade 2 KMI Students at Pondok Modern El-Haq Jombang: تقييم مهارة الكتابة (الإملاء) لدى طلاب الصف الثاني في معهد الحق للتربية الإسلامية الحديثة بجومبانج - Wahyudin, Abdullah Abas; Abd. Faishol; Muhammad Nanang Qosim (Ukazh : Journal of Arabic Studies, 2025)
This study aims to evaluate the actual performance of second-grade students of Madrasah Mu'allimin Islamiyah (KMI) at El Haq Modern Islamic Boarding School Jombang in writing skills (imla') and analyze their most frequent spelling errors. The researcher employed the descriptive analytical method, relying on a standardized dictation test as the main data collection instrument from a sample of (48) students selected randomly. The findings indicate that the mean score of the students' performance was (63.75), categorizing their general achievement level as "Good". Error analysis revealed that more than two-thirds of the errors are concentrated in two primary areas: writing hamzah in its various forms (38.5% of total errors) and writing alif layyinah (soft alif) at the end of words (25.2%). This data clearly suggests that the core challenge lies not in general neglect, but in the lack of connection between complex morphological rules (sarf) (such as the strongest vowel rule or root origin) and writing practice. The study recommends the necessity of integrating intensive remedial training programs focusing on the phonetic and morphological analysis of words.